PERAN UNIVERSITAS DALAM PENGEMBANGAN INDUSTRI KECIL UNTUK MENINGKATKAN DAYA SAING EKONOMI LOKAL DI POLEHAN MALANG - Vidya Purnamasari; Vika Annisa Qurrata; Sudjatmiko Sudjatmiko (University of Merdeka Malang, 2019)
The majority of Small and Medium Enterprises (SMEs) in Malang is facing several problems, namely the lack of technology and innovation in terms of quality in production and marketing. In order to improve the competitiveness of the local economy of SMEs in Polehan Village, Malang State University through DRPM funding, it provides facilities assistance, online marketing training and business management. This activity is carried out with the intention that SMEs can be more competitive and independent for business development. In detail, the form of activities is to increase the application of science and technology in society through the design of operational training for large ball sewing machines, marketing through the Tokopedia marketplace, and business management. The results that have been achieved are increased marketing so that products / goods in the form of: footwear made from cow, sheep and snake skin can be distributed evenly through e-commerce. E-commerce used is the marketplace and Google MyBusiness which are currently in great demand by consumers. DOI: https://doi.org/10.26905/abdimas.v4i2.3560